The role of hypoxia in stem cell potency and differentiation. (November 2013) - Hawkins, Kate E; Sharp, Tyson V; McKay, Tristan R
Regenerative medicine relies on harnessing the capacity of stem cells to grow, divide and differentiate safely and predictably. This may be in the context of expanding stem cells in vitro or encouraging their expansion, mobilization and capacity to regenerate tissues either locally or remotely in vivo . In either case, understanding the stem cell niche is fundamental to recapitulating or manipulating conditions to enable therapy. It has become obvious that hypoxia plays a fundamental role in the maintenance of the stem cell niche. Low O2 benefits the self-renewal of human embryonic, hematopoietic, mesenchymal and neural stem cells, as well as improving the efficiency of genetic reprogramming to induced pluripotency. There is emerging evidence that harnessing or manipulating the hypoxic response can result in safer, more efficacious methodologies for regenerative medicine.